2016
DOI: 10.1177/0363546516660062
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Revision Surgery After Anterior Cruciate Ligament Reconstruction

Abstract: Background: Arthroscopically assisted anterior cruciate ligament (ACL) reconstruction is a common orthopaedic procedure. Graft failure after reconstruction remains a devastating complication, often requiring revision surgery and less aggressive or modified rehabilitation. Worse functional and patient-reported outcomes are reported compared with primary reconstruction. Moreover, both rates and risk factors for revision are variable and inconsistent within the literature. Purpose: To determine the rate of revisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 35 publications
(42 reference statements)
2
32
2
Order By: Relevance
“…There is a possibility that other biological factors play a part too; however, this is not confirmed in current literature. The association between younger patient age and increased risk of graft failure and revision surgery is well established in current literature [ 2 , 9 , 14 , 17 , 18 , 22 , 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a possibility that other biological factors play a part too; however, this is not confirmed in current literature. The association between younger patient age and increased risk of graft failure and revision surgery is well established in current literature [ 2 , 9 , 14 , 17 , 18 , 22 , 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported increasing age to be a protective factor against revision ACLR, 111 114 and the average time between primary ACLR and revision ACLR ranges from 1.5 to 3.5 years in the literature. 111 114 115 116 117 118 Some graft processing techniques as well as increased graft irradiation (>1.8 Mrad) have been associated with higher revision rates. 118 In a retrospective analysis, posterior tibial tunnel placement (placement 50% or more posterior to Amis and Jakob line) has also been associated with increased revision rates in those using a 70° “anti-impingement” tibial tunnel guide.…”
Section: Risk Factors For Revision Anterior Cruciate Ligament Reconstmentioning
confidence: 99%
“…In recent years ACL repair with different techniques is being performed. The early outcome studies show some promises, however a revision rate of 18% after repair in the two first years is higher than with the revision rate after reconstruction (3.6%) [ 19 20 ]. Imaging findings after these new repair techniques are still unchartered territory.…”
Section: Anterior Cruciate Ligament (Acl) Imagingmentioning
confidence: 99%